Is induction of labour by Propess® safe? A comparison of midwife-led versus obstetrician-led labour management. (May 2015) - Bayoglu Tekin, Y.; Mete Ural, U.; Kerimoglu, O. Secilmis; Balik, G.; Kir Sahin, F.; Guvendag Guven, E. S.
Abstract: This retrospective study compared maternal and fetal outcomes after labour induction, using a dinoprostone vaginal pessary (Propess ® ) in midwife-led and obstetrician-led labour management. Labour induction outcomes, delivery mode and rates of admission to the neonatal intensive care unit were compared. A total of 405 women, 40.5% ( n = 164) from midwife-led units and 59.5% ( n = 241) from an obstetrician-led unit, participated. There was no statistically significant difference between the two groups in caesarean section rate or neonatal intensive care unit admission rates ( p = 0.789 and 0.769, respectively). Non-reassuring fetal non-stress test and uterine hyperstimulation risks were higher in the obstetrician-led unit ( p = 0.003 and 0.001, respectively, and odds ratio (OR) 0.165, 95% CI: 0.117–0.232 and OR 0.218, 95% CI: 0.078–0.611, respectively). Postpartum blood transfusion rate was higher in the midwife-led units ( p = 0.002, OR 8.082, 95% CI: 1.879–39.292). Labour induction with Propess ® is safe during both midwife-led and obstetrician-led labour management.